Discovery of Phosphatidic Acid, Phosphatidylcholine, and Phosphatidylserine as Biomarkers for Early Diagnosis of Endometriosis - Li, Jingjie; Gao, Yue; Guan, Lihuan; Zhang, Huizhen; Sun, Jiahong; Gong, Xiao; Li, Dongshun; Chen, Pan; Ma, Zheng; Liang, Xiaoyan; Huang, Min; Bi, Huichang (Frontiers in Physiology, 2018)
The sensitivity and specificity of clinical diagnostic indicators and noninvasive diagnostic methods for endometriosis at early stage is not optimal. Previous studies demonstrated that abnormal lipid metabolism was involved in the pathological development of endometriosis. Our cross-sectional study included 21 patients with laparoscopically confirmed endometriosis at stage I-II and 20 infertile women who underwent diagnostic laparoscopy combined with hysteroscopy from January 2014 to January 2015. Eutopic endometrium was collected by pipelle endometrial biopsy. Lipid metabolites were quantified by ultra high performance liquid chromatography coupled with electrospray ionization high-resolution mass spectrometry (UHPLC-ESI-HRMS). Lipid profiles of endometriosis patients at early stage (I-II) was characterized by a decreased concentration of phosphatidylcholine (18:1/22:6), (20:1/14:1), (20:3/20:4) and phosphatidylserine (20:3/23:1) and an increased concentration of phosphatidic acid (25:5/22:6) compared with control. The synthesized predicting strategy with 5 biomarkers has a specificity of 75.0% and a sensitivity of 90.5%. Lipid profile of eutopic endometrium in endometriosis was effectively characterized by UHPLC-ESI-HRMS–based metabolomics. Our study demonstrated the alteration of phosphatidic acid, phosphatidylcholine, phosphatidylserine metabolites in endometriosis and provided potential biomarkers for semi-invasive diagnose of endometriosis at early stage.